Influence of External Coagulant Water Types on the Performances of PES Ultrafiltration Membranes - He, Jing; Ji, Lingyun; Shi, Baoli (Journal of Membrane and Separation Technology, 2012)
In order to research the influence of cluster structure on the performances of membranes prepared through immersion precipitation phase inversion technique when water was used as external coagulant, in this paper, two types of water were prepared from distilled water and were used as external coagulant at room temperature. One type (water I) was prepared from boiled distilled water and another type (water II) was prepared from ice. Six polyethersulfone membranes were prepared by using polyvinylpyrrolidone as additive. Pure water flux, permeation flux of BSA solution and rejection to bovine serum albumin of the membranes were investigated. It was found that according to the statistically experimental results, the membranes prepared in water II always had larger pure water flux, permeation flux of BSA solution, rejection and swelling ratio than the membranes prepared in water I. Consequently, the types of water external coagulant had some influences on the separation performances of the prepared membranes but had no effects on the surface chemical groups. However, the present morphology characterization technology, such as SEM couldn’t detect the tiny difference in the pore structures.